High performance, direct drive machines for aerospace applications - Galea, Michael (2013)
For aerospace related electric systems, torque/force density, reliability and fault tolerance are of the utmost importance. A method by which high figures of reliability can be achieved is by eliminating any mechanical gearing or interconnection elements between the electrical machine and its mechanical load. This means that direct drive, electrical machines must be employed. However, to implement such solutions (without any mechanical advantages), electrical machines with excellent torque density (for rotational machines) and force density (for linear machines) performances are required.